7 Psychological Characteristics that Influence Customer’s Buying Decision to Mitsubishi Pajero Sport Bandung Institute of Technology (SBM-ITB) - Suhadi, Rachmat; Wandebori, Harimukti (Journal of Business and Management, 2012)
As one of the world's largest automotive company, Mitsubishi has high sales in developing countries such as Indonesia. In the beginning, Mitsubishi was an automotive company that focused on diesel vehicles and heavy equipments, such as trucks, buses and tractors. However, Mitsubishi sought to change its past image into a new image that can compete against its main competitors, such as Toyota and Honda, on the passenger vehicle sector. Recently, Mitsubishi unveiled its newest product, Mitsubishi Pajero Sport. Gradually, Mitsubishi changed their former brand image into a newer, yet still powerful image. On automotive media assessments, Mitsubishi Pajero Sport always gets high points on its performance yet until 2011, Mitsubishi sales always below Toyota’s, Mitsubishi’s main competitor. By using Regression Analysis, Factor Analysis and Cluster Analysis, the author wants to find out what psychological characteristics that can be used as guidelines by Mitsubishi in selling its products. The result of the regression analysis shows that the influence of psychological characteristics on purchase decisions is 18.15%.  On the other hand, the factor analysis that associated with various psychological theories, will show how seven psychological characteristics can influence the customer’s decision to buy Mitsubishi Pajero Sport. Those seven psychological characteristics are Psychological Value of Money, Relationship to Human and Environment, Brand Loyalty, Self Confidence and Expectancy, Personality of Customer, Leadership Confidence and Self Esteem and Risk.  Cluster analysis of existing variable split into 3 clusters, the researchers compared the results of factor analysis and cluster analysis and choosing factor analysis to determine that it is easier to describe the psychological characteristics of the customer. By knowing the seven psychological characteristics of the customers,  Mitsubishi will have more specific marketing strategy to sell its products and also more specific on determining the target market of its flagship product,  Mitsubishi Pajero Sport. Key words: Brand Image, 7 Psychological Characteristics , Reggression Analysis, Factor Analysis, Cluster Analysis, Specific Target Market, Specific Marketing Strategy